Isolation and screening producing growth regulator cyanobacteria strains - Thi Oanh, Doan; Thi Thuy, Duong; Thi Thu Lien, Nguyen; Thi Mai Anh, Dang; Thi Quynh, Hoang; Minh Thang, Hoang; Thi Nguyet, Vu; Phuong Quynh, Le Thi (Vietnam Journal of Biotechnology, 2020)
Cyanobacteria are photosynthetic microorganisms that have their biosynthesis capacities for secondary compounds with the high application value. They can produce a variety of bioactive compounds such as lipopeptides, fatty acids, toxins, carotenoids, vitamins and plant growth regulators which could be released into the culture medium. The present study aimed to isolate and screen cyanobacteria strains that could synthesize phytohormone, indole-3-acetic acid (IAA) from paddy soild and fresh water ecosystems (canals, river). Soil and water samples were collected from diferent provinces (Bac Giang, Thanh Hoa and Hue). Indole-3-acetic acid was extracted from the culture of isolated cyanobacteria strains and identified using the Salkowski method. As a result, total 10 strains belonging to 4 genera including Nostoc, Anabena, Geitlerinema and Planktothricoides were susscessful isolated from river, canal and rice field. The morphology of isolated taxa was characterized and monoalgal cultures were grown in BG 11 medium. In L-tryptophan-enriched growth media, all cyanobacteria strains in this research were able to biosynthesize growth regulators with IAA concentrations ranging from 9.1 to 95 µg/mL. Among the isolated cyanobacteria strains, the Planktothricoides raciborskii showed potential for the production of IAA even in the absence of tryptophan in the culture medium. Research results of the L-tryptophan concentration effect on the ability of IAA biosynthesis of this cyanobacteria strain showed that IAA concentration increased gradually and reached the highest value (118,28 ± 2,00 µg/mL) when supplementing L- tryptophan in culture medium at 900 µg/mL. The capacity of producing IAA makes these isolated cyanobacteria an appopriate cadidate for agricultural biotechnology